UPAYA BAKOR PAKEM DALAM MENCEGAH PERKEMBANGAN POTENSI RADIKALISME DI KABUPATEN KEPAHIANG - Muhammad Ridwan (Manthiq : Jurnal Filsafat Agama dan Pemikiran Islam, 2016)
Abstract: Background This study is a radical  ideology  as a basis  for the  alleged  terror  bombing. Indonesia makes this ideology as it feared  more  widespread. Kepahiang District participated prevent  this ideology does not  escalate. Formulation of the  problem in this research is: How Bakor  Pakem efforts  in preventing the development potential of radicalism in the District Kepahiang?.  This study examined the potential radicalism in Kepahiang and  preventive  measures by Bakor  Pakem. This type  of study  is a qualitative  research with descriptive and  analytical  nature. The  study  found  that  there  is a potential Kepahiang District of religious radicalism. Some  residents Kepahiang is a member of the  organization Hizb ut-Tahrir Indonesia (HTI), the Islamic Defenders Front (FPI) and the former followers of the Movement Fajar Nusantara (Gafatar).  While in Kepahiang yet these organizations.Preventive measures that do Bakor Pakem are: first, to collect information that will be members of Bakor Pakem ranging from intelligence work by the police (Police) and the Indonesian Military (Kodim and  Koramil). Second, the monthly  reports  submitted by the Office of National and  Political Unity government Kepahiang District. The third discussion meeting held  as chairman of the  State  Attorney Bakor Bakor Pakem Pakem with members. Fourth. Prevention is done by each agency and organization Bakor Pakem corresponding basic  tasks and functions  of each.  The Police with intelligence work and guidance of the community, the military intelligence and  guidance of an integrated, the Ministry of Religious Affairs with public  education, the  Indonesian Ulema  Council  with public  education, the  Forum  for Religious Harmony (FKUB) with coordination and communication between religious communities and socialize together involve berbegai elements of society, And the declaration of refusal schools  of ISIS and  radicalism involving various organizations and educational institutions.